Cover Image. (22nd August 2022) - Guo, Rui; Si, Dongyue; Chen, Zhensen; Dai, Erpeng; Chen, Shuo; Herzka, Daniel A.; Luo, Jianwen; Ding, Haiyan
Abstract : The cover image is based on the Research Article SAturation‐recovery and Variable‐flip‐Angle‐based three‐dimensional free‐breathing cardiovascular magnetic resonance T1 mapping by Rui Guo et al., https://doi.org/10.1002/nbm.4755 .